Binding of the repressor complex REST‐mSIN3b by small molecules restores neuronal gene transcription in Huntington's disease models. (19th July 2013) - Conforti, Paola; Zuccato, Chiara; Gaudenzi, Germano; Ieraci, Alessandro; Camnasio, Stefano; Buckley, Noel J.; Mutti, Cesare; Cotelli, Franco; Contini, Alessandro; Cattaneo, Elena
Abstract: Transcriptional dysregulation is a hallmark of Huntington's disease (HD) and one cause of this dysregulation is enhanced activity of the REST‐mSIN3a‐mSIN3b‐CoREST‐HDAC repressor complex, which silences transcription through REST binding to the RE1/NRSE silencer. Normally, huntingtin (HTT) prevents this binding, allowing expressing of REST target genes. Here, we aimed to identify HTT mimetics that disrupt REST complex formation in HD. From a structure‐based virtual screening of 7 million molecules, we selected 94 compounds predicted to interfere with REST complex formation by targeting the PAH1 domain of mSIN3b. Primary screening using DiaNRSELuc8 cells revealed two classes of compounds causing a greater than two‐fold increase in luciferase. In particular, quinolone‐like compound 91 (C91) at a non‐toxic nanomolar concentration reduced mSIN3b nuclear entry and occupancy at the RE1/NRSE within the Bdnf locus, and restored brain‐derived neurotrophic factor (BDNF) protein levels in HD cells. The mRNA levels of other RE1/NRSE‐regulated genes were similarly increased while non‐REST‐regulated genes were unaffected. C91 stimulated REST‐regulated gene expression in HTT‐knockdown Zebrafish and increased BDNF mRNA in the presence of mutant HTT. Thus, a combination of virtual screening and biological approaches can lead to compounds reducing REST complex formation, which may be useful in HD and in other pathological conditions. Dysregulation of REST and its target genes have been implicated in Huntington's disease. We have coupled structured‐based virtual screening approaches to biological assays and selected molecules that interfere with the repressor complex REST‐mSIN3b. In particular, at the non‐toxic dose, compound C91 is able to increase neuronal gene transcription and to reverse low Bdnf mRNA levels in HD models. Abstract : Dysregulation of REST and its target genes have been implicated in Huntington's disease. We have coupled structured‐based virtual screening approaches to biological assays and selected molecules that interfere with the repressor complex REST‐mSIN3b. In particular, at the non‐toxic dose, compound C91 is able to increase neuronal gene transcription and to reverse low Bdnf mRNA levels in HD models.